The potential for storing carbon by harvested wood products - Zhao, Jianheng; Wei, Xinyuan; Li, Ling (Frontiers in Forests and Global Change, 2022)
Forest ecosystems are a critical component of the global carbon cycle, which stores carbon in both vegetation biomass and soil organic matter. Timber harvesting can laterally move the carbon stored in forest sectors to harvested wood products (HWPs) and thus create an HWPs carbon pool. The carbon stored in HWPs is allocated to end-use wood products (e.g., paper, furniture), landfill (e.g., waste wood materials), and charcoal (e.g., non-energy use biochar). Environmental change is predicted to have far-reaching effects on the carbon stored in HWPs by altering the timber supply. In addition, technological advancement in the wood industry accelerates the carbon inflow rate by promoting processing efficiency and reduces the outflow rate by creating innovative wood products with a longer service life. Socioeconomic factors such as population and household income also contribute to the carbon stock changes in wood products by expanding or reducing the demand. Given numerous factors that are correlated with the size of HWPs carbon pool, an advanced and comprehensive understanding of these factor on modifying the HWPs carbon storage is essential to modeling and predicting the carbon stored in HWPs, atmospheric CO2 concentration, and global warming; therefore, we reviewed, summarized, and discussed the function of these factors in regulating the carbon stored in HWPs.